Structural MRI biomarkers for preclinical and mild Alzheimer's disease - Fennema-Notestine, Christine; Hagler Jr, Donald J.; McEvoy, Linda K.; Fleisher, Adam S.; Wu, Elaine H.; Karow, David S.; Dale, Anders M. (Human brain mapping, 2009)
Noninvasive MRI biomarkers for Alzheimer's disease (AD) may enable earlier clinical diagnosis and the monitoring of therapeutic effectiveness. To assess potential neuroimaging biomarkers, the Alzheimer's Disease Neuroimaging Initiative is following normal controls (NC) and individuals with mild cognitive impairment (MCI) or AD. We applied high‐throughput image analyses procedures to these data to demonstrate the feasibility of detecting subtle structural changes in prodromal AD. Raw DICOM scans (139 NC, 175 MCI, and 84 AD) were downloaded for analysis. Volumetric segmentation and cortical surface reconstruction produced continuous cortical surface maps and region‐of‐interest (ROI) measures. The MCI cohort was subdivided into single‐ (SMCI) and multiple‐domain MCI (MMCI) based on neuropsychological performance. Repeated measures analyses of covariance were used to examine group and hemispheric effects while controlling for age, sex, and, for volumetric measures, intracranial vault. ROI analyses showed group differences for ventricular, temporal, posterior and rostral anterior cingulate, posterior parietal, and frontal regions. SMCI and NC differed within temporal, rostral posterior cingulate, inferior parietal, precuneus, and caudal midfrontal regions. With MMCI and AD, greater differences were evident in these regions and additional frontal and retrosplenial cortices; evidence for non‐AD pathology in MMCI also was suggested. Mesial temporal right‐dominant asymmetries were evident and did not interact with diagnosis. Our findings demonstrate that high‐throughput methods provide numerous measures to detect subtle effects of prodromal AD, suggesting early and later stages of the preclinical state in this cross‐sectional sample. These methods will enable a more complete longitudinal characterization and allow us to identify changes that are predictive of conversion to AD. Hum Brain Mapp 2009. © 2009 Wiley‐Liss, Inc.